(Geo)Demografie nejen pro ekonomy - Kunc, Josef (Masaryk University Press, 2019)
Title in English: (Geo)Demography not only for economists The publication is intended primarily for teaching the subject Demography, which takes place in the bachelor study program Regional Development and Tourism at ESF MU. Its further use can be found in other programs and branches of economically or naturally oriented faculties. The form of the text is oriented to the form of a university text, the content combines elements of demographic analysis and regional demography with an emphasis on the study of populations or more precisely inhabitants of state units, regions and macro-regions and interpretations of their spatial, economic and socio-cultural similarities and differences.